2021
DOI: 10.1016/j.ijcha.2021.100777
|View full text |Cite
|
Sign up to set email alerts
|

Research progress on the molecular mechanism of coronary microvascular endothelial cell dysfunction

Abstract: Coronary microvascular disease is a high-risk factor for many cardiovascular events. However, due to its high concealment and many etiologies, the current understanding of its pathophysiological mechanism is very limited, which greatly limits its clinical diagnosis and treatment. In the process of the occurrence and development of coronary microvascular disease, the damage of coronary microvascular endothelial cell (CMEC) is the core link. CMEC's stress, metabolism, inflammation and other dysfunctions have a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“…ET-1 and NO are vasoactive substances that synthesize endothelial cells, whose synthesis, release and imbalance directly affect the basic tension of blood vessels, and are closely related to the occurrence and development of CHD. [39] Our meta-analysis suggested that ZXGD significantly decreased ET-1 and increased NO. Studies have shown that inflammatory response actives an important part in changing coronary plaques.…”
Section: Discussionmentioning
confidence: 98%
“…ET-1 and NO are vasoactive substances that synthesize endothelial cells, whose synthesis, release and imbalance directly affect the basic tension of blood vessels, and are closely related to the occurrence and development of CHD. [39] Our meta-analysis suggested that ZXGD significantly decreased ET-1 and increased NO. Studies have shown that inflammatory response actives an important part in changing coronary plaques.…”
Section: Discussionmentioning
confidence: 98%
“… 52 DM also decreases endothelial prostacyclin secretion, impairs fibrinolytic ability, alters endothelium-dependent hyperpolarizing factor-mediated responses, increases procoagulant activity, increases production of growth factors and extracellular matrix (ECM) proteins, and increases endothelial permeability, all contributing factor for CMD. 12 , 52 55 Simultaneously, due to altered calcium transport and accumulation, the mitochondrial transition pores open, causing cardiomyocyte apoptosis. 56 The elevated level of Ca 2+ plays a role in the activation of NADPH oxidase and ROS overproduction.…”
Section: Targeting Oxidative Stress In the Cardiac Cellsmentioning
confidence: 99%
“…These alterations markedly increase the risk of severe cardiovascular events like exertional angina or myocardial ischemia. 12 Additionally, DM also increases the risk of HF with preserved ejection fraction (HFpEF), a condition in which heart filling deficits are noted. 13 Meta-analysis has shown that 50% of diabetic patients are at heightened risk of developing HFpEF compared to non-diabetic patients.…”
Section: Introductionmentioning
confidence: 99%
“…Structural or functional damage to coronary microvascular endothelial cells (CMECs) is a key mechanism in the occurrence and development of CMD [ 37 ]. Abnormalities in CMECs, which account for approximately 1/3 of the total number of cells in the heart, lead to impaired cardiac microvascular vessel integrity and subsequent CMD [ 38 , 39 ].…”
Section: Endothelial Cell-mediated Correlation Between Coronary Micro...mentioning
confidence: 99%